Growth and income distribution in countries at intermediate stages of development - Eduardo Sarmiento P. (CEPAL Review, 1992)
This article analyses the relationship between growth and income distribution. The existence of a conflict between these two variables depends on a country’s level of development. Such conflicts arise during intermediate stages of development, when growth is led by savings, and tend to disappear when growth becomes a knowledge-led phenomenon. Part of the reason for this is that saving is much more concentrated than education and technology are. The author contends that the conflict is not insuperable, however; in practical terms, it can be corrected by means of fiscal and educational policy measures.